Detection the effectiveness of antagonism and its role in production of fungal toxin - Abed Ali, Wisam jasim; Hasan, Hamid Ghaffoori (International Journal of Psychosocial Rehabilitation, 2020)
Thirty-five samples of maize were collected from the local markets of Diwaniyah city , after the isolation, the results showed 16 isolated of fungi , including 7 isolates of F. moniliform .The susceptibility of these isolated was detected on the production of trichothecenes showed that 4 isolated have the ability to produced fungal toxin and varying concentrations (18 , 21 , 24 , 31)µg/kg. Trichoderma harzianum was showed the ability of inhibited the production of fungal toxin from F. moniliform, through the antagonism between it and F. moniliform.